Platelet lysates stimulate angiogenesis, neurogenesis and neuroprotection after stroke - Hayon, Yael; Dashevsky, Olga; Shai, Ela; Varon, David; Leker, Ronen R. (Thrombosis and Haemostasis, 2013)
Platelets contain chemo-attractants and mitogens that have a major role in tissue repair. Therefore we hypothesised that tissue regeneration secondary to activation of endogenous neural stem cells (eNSC) can be enhanced by delivering platelets to the ischaemic brain. To examine these potential therapeutic effects we injected platelet-poor plasma (PPP), fibroblast growth factor (FGF2) and platelet lysate (PLT) to the lateral ventricles after permanent middle cerebral artery occlusion (PMCAO) in rats. The animals were tested with the neurological severity score, and infarct volumes were measured at 90 days post–PMCAO. Immunohistochemistry was used to determine the fate of newborn cells and to count blood vessels in the ischaemic brain. Platelets significantly increased eNSC proliferation and angiogenesis in the subventricular zone (SVZ) and in the peri-lesion cortex. Functional outcome was significantly improved and injury size was significantly reduced in rats treated with PLT suggesting additional neuroprotective effects. In conclusion, local delivery of PLT to the lateral ventricles induces angiogenesis, neurogenesis and neuroprotection and reduces behavioural deficits after brain ischaemia.
Keywords: Angiogenesis; neurogenesis; neuroprotection; platelets; cerebral ischaemia